Fiber optic based sensor for Ni2+. - Hong, Jesmond Xun Jie. (2013)
This study aimed to combine the use of a Mach-Zehnder type interferometer and the hydrogel volume phase transition theory to quantitatively model the refractive index dependence upon Ni2+ concentration. A highly sensitive refractive index sensor was achieved via fusion splicing, sandwiching a 3 cm photonic crystal fiber (PCF) longitudinally in the middle of two SMFs. The fully collapsed air holes at localized regions allowed the coupling of various modes and a red shift was detected when the fiber was subjected to medium of increasing refractive index. A poly-acrylamide hydrogel was then coated onto the PCF interferometer via a free radical polymerization mechanism. A novel method of copolymerizing glycidyl methacrylate with the monomer and cross-linkers incorporated epoxy groups as molecular recognition agents for 5-amino-8-hydroxyquinoline. At low concentration of Ni2+, the heavy metal form bisligand complexes with 8-hydroxyquinoline and serves as additional cross-linkages to the hydrogel, thereby causing it to shrink. At high concentration of Ni2+ however, Ni2+ bind to the ligand with a 1:1 ratio and break the cross-linkages, causing the hydrogel to swell. This Ni2+ induced hydrogel swelling and shrinkage manifests as a RI change, and can be transduced to an optical signal using the Mach-Zehnder type interferometer.